SimSelect: Similarity-based selection for 3D surfaces - Guy, Emilie; Thiery, Jean-Marc; Boubekeur, Tamy (Computer graphics forum, 2014)
Surface selection is one of the fundamental interactions in shape modeling. In the case of complex models, this task is often tedious for at least two reasons: firstly the local geometry of a given region may be hard to manually select and needs great accuracy; secondly the selection process may have to be repeated a large number of times for similar regions requiring similar subsequent editing. We propose SimSelect, a new system for interactive selection on 3D surfaces addressing these two issues. We cope with the accuracy issue by classifying selections in different types, namely components, parts and patches for which we independently optimize the selection process. Second, we address the repetitiveness issue by introducing an expansion process based on shape recognition which automatically retrieves potential selections similar to the user‐defined one. As a result, our system provides the user with a compact set of simple interaction primitives providing a smooth select‐and‐edit workflow.